Examining hierarchical importance of competitive strategy components of Penang Port of Malaysia: A preliminary study - Subhan, Muhammad; Nik Abdullah, Nik Ab. Halim (Medwell Journals, 2015)
This study is aimed at investigating the importance of Porter’s competitive strategy components for main seaport in the Northern Corridor Economic Region (NCER), the Penang Port.This study examines, priority perspectives on the competitive strategy components from various relevant experts or academia using the Analytic Hierarchy Process (AHP) approach.The data were gathered from a study conducted within the NCRC research grant project.About 3 components of Porter’s competitive strategy, namely; cost leadership, focus and differentiation were examined.The findings show the hierarchy of importance for each component to be considered by Penang Port authority.This study highlights new implications of using appropriate competitive strategy for Penang Port growth based on its hierarchical approach.